PECULIARITIES OF THE SURFACE FLAW DETECTION BY ELASTIC WAVES SIMULATED BY PULSE-LASER RADIATION - А. R. Bаеv; A. I. Мitkovets; D. A Коstiuk; G. E. Konovalov (Приборы и методы измерений)
Laser pulse simulation of the surface waves and its receiving by contact piezoelectric probes is perspective direction to detect surface defects. The aim of this work was to determine optimal conditions for detection of the real fatigue cracks of nearly microns width and surface pores by moving depending on the position of the center of a laser beam laser beam spot. The objects of research were metal specimens with crack’s width of 8 m up to 0,5 mm and depth ≈ 400– 500 mm up to ≈ 200 mm. Cylindrical hole by ≈ 1 mm diameter used as a model pore. An experimental installation used consisted of the pulse laser light emission source with laser wavelength of 1.06 m and laser pulse duration of ≈ 20 ns. An arrangement to adjust the laser beam spot geometry in the form of a long strip and a circle was applied. Surface waves were received by the 2.7 MHz frequency probe, and processed with use of a «Spectronic» TDS 3052B oscilloscope. The laws of acoustical signal amplitude and its form changes vs. the laser beam spot geometry and its position in regard to defect were determined. We discovered that optimal conditions for flaw detection took place when the laser beam spot moving trough the defect’s range – crack and pore. In the first case amplitude growth of the signal was up to 7–8 time – like as resonance conditions realized. And the ratio of the laser’s beam spot width (as long strip) to wave length were ≈ 1.8–2.2. The more informative parameter to find crack with small width (≈ 0.5mm) was the acoustical pulse spectrum or the pulse entrance part. Thus, the further increasing of the surface flaw detection may be realized by laser simulation of the surface waves controlling the form of the moving spot of laser beam. New possibilities to increase sensitivity and reliability of ultrasonic evaluation surfaces in objects with complicated profile and fare accessible places are to be arise.